(untitled) (Global Journal of Management and Business Research, 2020)
This paper sets out to explore the ability of consumers in a context of poverty to be cocreators of value Of the semi-structural interviews that were conducted with a sample of 30 consumers it appears that the concept of socially responsible consumer is only partially perceived inasmuch as very often the purchasing and consumption decisions of consumers do not take into account social and or environmental concerns but are dictated by survival mechanisms It cannot therefore act as a socially committed actor capable of influencing the opportunistic behaviors of companies Some conditions are therefore necessary for this consumer to develop activist behaviors